Association of high cortisol levels in pregnancy and altered fetal growth. Results from the MAASTHI, a prospective cohort study, Bengaluru - Shriyan, Prafulla (Lancet Reg Health Southeast Asia, 2023)
BACKGROUND: The role of maternal stress levels on mothers’ mental health and fetal growth has been previously studied. However, the evidence linking cortisol exposure during pregnancy to growth outcomes in infants is sparsely available from lower and middle-income countries. We aim to investigate the association of serum cortisol levels in pregnancy with infant birth outcomes and postpartum depressive symptoms in a public health facility in India. METHODS: The current study is a part of the maternal antecedents of adiposity and studying the transgenerational role of hyperglycemia and insulin (MAASTHI) prospective cohort. We assessed the relationship between maternal exposure to serum cortisol and adverse neonatal outcomes and postpartum depressive symptoms. Serum cortisol levels in stored blood samples were measured in 230 pregnant women as a biomarker for stress during pregnancy. Pregnant women between 18 and 45 years of age were recruited for the study, presenting at ≥14 weeks of gestation and providing voluntary written informed consent. The Edinburgh Postnatal Depression Scale assessed postpartum depressive symptoms, and detailed infant anthropometric measurements were carried out at birth. FINDINGS: We found that higher levels (>17.66 μg/L) are significantly associated with low birth weight (OR = 2.28; 95% CI 1.21–4.32) and lower weight for length (OR = 2.16; 95% CI 1.07–4.35). The odds of developing postpartum depressive symptoms in pregnant women with higher mean cortisol cut-off levels is 2.3-fold [OR: 2.33, 95% CI (1.17, 4.64)] compared than women with lower cortisol levels. No significant association was found between serum cortisol and infants' birth weight for gestational age, head circumference, the sum of skinfold thickness, and crown-rump length. INTERPRETATION: Our results support the hypothesis that higher maternal cortisol levels may adversely impact birth weight, weight for length in newborns, and postpartum depressive symptoms in mothers. FUNDING: This study was supported by the 10.13039/501100009053India Alliance Senior Fellowship [Grant No. IA/CPHS/20/1/505278] awarded to Giridhara R. Babu.